Impact, not impact factor - Razak, Dzulkifli Abd (2011)
THE year 2010 ended on a rather good note with the appointment of Malaysia's first three Distinguished Professors. Professor Tan Sri Mohd Kamal Hassan, Professor Datuk Shamsul Amri Baharuddin and Professor Dr Lai-Meng Looi are leading the way as announced by Higher Education Minister Datuk Seri Mohamed Khaled Nordin. More than the monetary perks they received, this accolade marked a new milestone in recognising scholarly personalities and achievements among Malaysians. The Distinguished Professors are role models who can be emulated, especially by the younger and future generations of a knowledge society that we aim to evolve into. For too long our idols have been celebrities with rather different lifestyles and, at times, values. These Distinguished Professors set another path to become a celebrity of the intellectual kind. This augurs well for Malaysia, which until now has yet to nurture a vibrant intellectual community.